Avaliacao nutricional de triathletes - Bassit, R. A.; Malverdi, M. A. (Revista Paulista Educação Física, 1998)
Triathlon is a good model for high intensity and prolonged exercise, in which the energy expenditure is pronounced. Very little is known, however, about the profile of Brazilian triathletes, as well as about their nutrition pattern. In this study we have evaluated the antropometric profile of Brazilian amateurs and professional triathletes, their nutrional pattern and their basic knowledge on nutrition. The results obtained showed that these athletes have a daily energy need of about 3730 kcal and 4250 kcal for amateurs and professionals, respectively. The dietary pattern assessment, however, showed that all of them presented a relatively high intake of fat, which could be substituted by an increased carbohydrate intake. All the athletes demonstrated a poor knowledge of basic nutrition, reflected in their dietary habits.